2016
DOI: 10.1002/ana.24754
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic microglial features in patients with hereditary diffuse leukoencephalopathy with spheroids

Abstract: The pathogenesis of HDLS seems to be associated with microglial vulnerability and morphological alterations. Ann Neurol 2016;80:554-565.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 29 publications
(42 reference statements)
8
60
0
Order By: Relevance
“…The molecular mechanism could involve suppression of mitophagy either directly (Ulland et al, 2017;Wang et al, 2019) or as an indirect consequence of overloading of the degradative pathway by the ingested myelin (Safaiyan et al, 2016). Furthermore, as observed in the mouse model ( Figure 5C), overexpression of TREM2 also occurs in the white matter of ALSP patients ( Figure 6E), where others have documented the presence of lipid-laden macrophages (Tada et al, 2016;Lin et al, 2010). Thus, decreased autophagy may contribute to ALSP pathology, and the benefits of stimulation of autophagy should be further explored.…”
Section: Discussionmentioning
confidence: 76%
“…The molecular mechanism could involve suppression of mitophagy either directly (Ulland et al, 2017;Wang et al, 2019) or as an indirect consequence of overloading of the degradative pathway by the ingested myelin (Safaiyan et al, 2016). Furthermore, as observed in the mouse model ( Figure 5C), overexpression of TREM2 also occurs in the white matter of ALSP patients ( Figure 6E), where others have documented the presence of lipid-laden macrophages (Tada et al, 2016;Lin et al, 2010). Thus, decreased autophagy may contribute to ALSP pathology, and the benefits of stimulation of autophagy should be further explored.…”
Section: Discussionmentioning
confidence: 76%
“…Of interest, both MSA [65][66][67] and HDLS [68] share pathological astro-and microgliosis. In a previous study we found that MSA patients had lower protein levels of G-CSF, a growth factor belonging to the same family as CSF, in the prefrontal cortex of MSA brains [20].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, deficiencies on key genes for the microglial survival and/or proliferation (such as CSF1R or TREM2) are associated with rare hereditary neurodegenerative diseases, such as adult-onset leukoencephalopathy with axonal spheroids or Nasu-Hakola disease (respectively) (Paloneva et al, 2000 , 2002 ; Chitu et al, 2016 ). In both diseases, the microglial response and, more relevant, the microglial survival seems to be compromised (Nataf et al, 2005 ; Satoh et al, 2011 ; Konno et al, 2014 ; Tada et al, 2016 ). On the other hand, missense mutations in TREM2 (such as R47H TREM2) produce an increases risk for late-onset AD (Guerreiro et al, 2013 ; Korvatska et al, 2015 ; Yeh et al, 2016 ) and a reduction in the number of microglial cells surrounding Aβ plaques in models.…”
Section: Soluble Phospho-tau Is Responsible For the Microglial Degenementioning
confidence: 99%